2019
DOI: 10.1038/s41388-019-0959-3
|View full text |Cite|
|
Sign up to set email alerts
|

TGLI1 transcription factor mediates breast cancer brain metastasis via activating metastasis-initiating cancer stem cells and astrocytes in the tumor microenvironment

Abstract: Mechanisms for breast cancer metastasis remain unclear. Whether truncated glioma-associated oncogene homolog 1 (TGLI1), a transcription factor known to promote angiogenesis, migration and invasion, plays any role in metastasis of any tumor type has never been investigated. In this study, results of two mouse models of breast cancer metastasis showed that ectopic expression of TGLI1, but not GLI1, promoted preferential metastasis to the brain. Conversely, selective TGLI1 knockdown using antisense oligonucleotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 40 publications
3
78
0
Order By: Relevance
“…We have optimized conditions to reliably separate two GLI1 isoforms by SDS-PAGE and validated custom-made antibodies to specifically detect tGLI1. However, the difficulty in separating the two proteins could mean that functions previously ascribed to GLI1 are actually due to tGLI1-specific activity [25,33]. Our laboratory, and others, have shown the tGLI1 variant to be expressed in most GBM specimens and patient-derived xenografts, but undetectable in normal brain cells or tissues [24,26,27,29].…”
Section: Glioblastomamentioning
confidence: 90%
See 1 more Smart Citation
“…We have optimized conditions to reliably separate two GLI1 isoforms by SDS-PAGE and validated custom-made antibodies to specifically detect tGLI1. However, the difficulty in separating the two proteins could mean that functions previously ascribed to GLI1 are actually due to tGLI1-specific activity [25,33]. Our laboratory, and others, have shown the tGLI1 variant to be expressed in most GBM specimens and patient-derived xenografts, but undetectable in normal brain cells or tissues [24,26,27,29].…”
Section: Glioblastomamentioning
confidence: 90%
“…GLI1 proteins regulate the expression of the pluripotency factors Nanog, octamer binding transcription factor 4 (OCT4), SOX2, WNT-2, CD44, and Kruppel-like factor 4 (KLF4) [148,165,167,168]. Recently, we have shown the novel tGLI1 isoform to promote the glioma stem cell population via upregulation of CD44 and the breast cancer stem cell population through upregulation of CD44, Nanog, OCT4, and Sox2 (Section 6) [31,33]. These data demonstrate that amplified SHH signaling is important for the self-renewal and maintenance of CSCs.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…42 TGLI1 may also contribute to radioresistance by increasing stemness and creating a "metastasis-friendly" microenvironment through activation of astrocytes. 42 Fatty acid binding protein 7 (FABP-7) is a lipid binding protein found specifically in the brain. However, FABP-7 is also expressed in BC cells, particularly Recent progress in the field of cell-and viral-based therapeutics has also been applied to HER2+ BCBrM.…”
Section: Mouse Models Of Her2+ Bcbrmmentioning
confidence: 99%
“…Cancer stem cells (CSCs) contributed to metastasis, recurrence and drug resistance in cancers [11][12][13][14], and previous data suggested that CSCs enrichment contributed to cisplatin-resistance in GC cells [17,18]. Therefore, elimination of CSCs will help to improve chemo-sensitivity in GC cells [19].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) were a subgroup of cancer cells characterized by high self-renewal abilities [11,12], which sustained the heterogeneity of tumor cells and contributed to metastasis and bad prognosis in GC patients [13,14]. In addition, recent data indicated that CSCs were pivotal for sustaining cisplatinresistance in multiple cancers, such as head and neck squamous cell carcinoma (HNSCC) [15], lung cancer [16] and GC [17,18].…”
Section: Introductionmentioning
confidence: 99%